Ginsenoside Rh2 Inhibits NLRP3 Inflammasome Activation and Improves Exosomes to Alleviate Hypoxia-Induced Myocardial Injury - Qi, Zhongwen; Yan, Zhipeng; Wang, Yueyao; Ji, Nan; Yang, Xiaoya; Zhang, Ao; Li, Meng; Xu, Fengqin; Zhang, Junping (Frontiers in Immunology, 2022)
The inflammatory microenvironment after acute myocardial infarction (MI) is a key limiting factor in the clinical application of stem cell transplantation and paracrine exosome therapy. Ginsenoside Rh2 (Rh2), a saponin ingredient of Qishen Yiqi Pills, exhibits a certain therapeutic effect on MI. However, the mechanism by which Rh2 alleviates the inflammatory microenvironment and improves the therapeutic efficiency of exosomes remains enigmatic. Here, we found that Rh2 attenuated the adverse effect of oxygen-glucose deprivation (OGD)-induced cellular injury, an in vitro pathological model of MI. Confocal microscopy observed that DiI-labeled BMSCs-derived exosomes exhibited an increased homing ability to cardiomyocytes, which, in turn, inhibited the nuclear translocation of NF-κB p65 and NLRP3 inflammasome activation, thereby alleviating the inflammatory microenvironment and further facilitating the homing of exosomes to cardiomyocytes by forming a feed-forward enhancement loop. In addition, we found that Rh2 was able to regulate the HMGB1/NF-κB signaling pathway to improve the OGD environment of cardiomyocytes, increasing the efficiency of the feed-forward loop. In conclusion, we find that Rh2 can improve the inflammatory microenvironment by enhancing the protection of exosomes against myocardial injury, providing new insights into the indirect modification of exosomes by Rh2 in MI treatment.